Faktor-faktor Yang Mempengaruhi Kemauan Untuk Membayar Pajak Wajib Pajak Badan Yang Terdaftar Di KPP Pratama Boyolali - Zulaikah, Anita Ermy; , Dra.Mujiyati,M.Si (2015)
This research aims to test awareness pay taxes , knowledge and understanding of the regulation of taxation , the perception of good over the effectiveness of the system of taxation and the quality of services to tax payers pay tax impact on the willingness .The population of this research is used in the tax agency listed in kpp boyolali pratama .The method by means of a method of sample collection purposive . That has collected data were analyzed using that data analysis done by testing the first classical prior to testing the hypothesis .In the classical testing of this research is a test of normality , heteroskedastisitas multikolinearitas test and test .Testing the hypothesis of using double linear regression analysis . The results of this research showed that the variable awareness pay taxes , knowledge and understanding of the regulation of taxation , the perception of good over the effectiveness of the system of taxation and the quality of services to taxpayers impact on the will pay taxes .The analysis of awareness of paying taxes obtained the value of 2,169 thitung & gt; of ttabel 2,048 , an analysis of knowledge and understanding of the regulation of taxation obtained the value of 2,067 thitung & gt; of ttabel 2,048 , an analysis of the perception of good over the effectiveness of taxation systems thitung obtained the value of 2,141 & gt; of ttabel 2,048 and analysis of the quality of services to taxpayers obtained the value of 2,440 thitung & gt; of ttabel 2,048 .